Maqashid Al-Syariah as a Contemporary Economic Solution According to Yusuf Al-Qaradawi - Hikmah, Nurul; Yazid, Muhammad (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This study explores the role of Maqashid Al-Shariah in addressing contemporary economic challenges. It examines Yusuf Al-Qaradawi's perspective on applying Islamic principles to achieve a just and equitable economic system. The research analyzes Al-Qaradawi's views on poverty, wealth inequality, and riba (interest), emphasizing the importance of Maqashid Al-Shariah in promoting social justice and ethical economic practices.  The study employs a qualitative approach, analyzing Al-Qaradawi's writings and relevant literature on Islamic economics. It investigates the application of Maqashid Al-Shariah in various economic contexts, including Islamic finance, resource distribution, and trade. The findings highlight the potential of Maqashid Al-Shariah to guide economic policies toward achieving common welfare (maslahah) and avoiding harm (mafsadah). The study concludes that Al-Qaradawi's approach offers valuable insights for building a more just and sustainable economic system, particularly in the face of globalization and financial crises.